The disappearance of three archaeophyte species in Hungary can be explained by their marked sensitivity to fertilizers - Ecseri, Károly; Mosonyi, István Dániel; Tilly-Mándy, Andrea; Honfi, Péter (Acta Biologica Szegediensis, 2017)
The archaeophytes are the component of segetal plant communities, and ensure biodiversity in arable field margins. Unfortunately, the number of these species decreased in the last decades because of the changing structure of agricultural production and increasing chemical application. In this study, the fertilizer sensitivity of three archaeophyte species was characterized using germination test, outdoor observation and proline content measurement. Papaver rhoeas had the most favourable germination parameters with promptness indices (1.5-14.0) and germination rates (0.39-0.81) decreasing with the concentration of fertilizer. On the other hand, mean germination time (7.32-10.03 days) decreased with elevated fertilizer concentration. Consolida regalis was characterized by the weakest development in laboratory. Slow early development was detected in case of Cyanus segetum (promptness index: 0.25-1.75; mean germination time: 12-13 days). Co. regalis responded to fertilization with higher blooming intensity. The proline accumulation indicated pronounced salt sensitivity of Cy. segetum (0.49-0.54 mg/100 mg), which could be one reason of the disappearance of this species from fields under cultivation. Our results suggest that at least Co. regalis and Cy. segetum are highly sensitive to mineral fertilizers and hence natural protection techniques for example arable weed margins must be widely used to block the disappearance of those species.